Partial Irreversible Demagnetization Reduction of Permanent Magnet Synchronous Motor - Mokhtar, Nur Hadibah; Aziz, Roziah (Evolution in Electrical and Electronic Engineering, 2022)
Synchronous motors are widely used nowadays in both high and low-speed applications. There are many types of the synchronous motor such as hysteresis synchronous motor (HSM), reluctance synchronous motor (RSM), permanent magnets synchronous motor (PMSM) and direct current (DC) excited synchronous motor. In this study, PMSM has been chosen since the life span of the chosen motor decreased due to the presence of demagnetization. This may be caused by the high temperature of the motor and the high magnitude of the current. Thus, this study aims to minimise the demagnetization value of PMSM using JMAG software. The partial irreversible demagnetization was applied to the permanent magnet. It is partial demagnetization since only some part of the permanent magnet has demagnetised. So, two designs have been proposed by adjusting the configuration of the permanent magnet. The comparison between the original design and two proposed designs had been explained clearly in this report. As the result, the proposed designs are able to minimise the value of demagnetization but the performance of PMSM decreased as well.